Pendampingan Gerakan Literasi Pada Taman Bacaan Masyarakat (TBM) Griyo Moco Kecamatan Watukumpul - Ilma Nafiyah; Misel Yulianti; Aryani Eka Sulistiya; Hendri Hermawan Adinugraha (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
The low literacy or reading interest of children in the Watukumpul sub-district, precisely in the village of Majalangu, is caused by children who are more likely to choose to play and gather together to play online games. Technological sophistication is one of the factors for the lack of literacy in children in Watukumpul District and the lack of motivation in children which causes low literacy. The existence of this service is expected to provide understanding and knowledge to children and can improve literacy skills. The method used is direct assistance with an educational approach. From this assistance, the children in Majalangu Village, Watukumpul Subdistrict have the motivation to improve literacy, besides that the children are also enthusiastic because of their high curiosity.